Mitologi sebagai Kearifan Ekologis Masyarakat Wawowae - Paula Mao, Leonarda; Sudiarna, I Gusti Putu; Aliffiati, Aliffiati (Sunari Penjor : Journal of Anthropology; Vol 3 No 1 (2019), 2021)
Wawowae Village is one of the villages in Ngada Regency, East Nusa Tenggara. This village has a mythology in the forest of Watuata where everything in the forest is associated with humans, animals, names of places and plants. So that all activities undertaken by the Wawowae people in the forest, must go through a process of ritual. This research aims to identify mythology in the forest of Watuata and its meaning, community perception, and forest conservation actions undertaken by the society. The study used the ethnoecological approach and Clifford Geertz's Interpretative theory to see the mythological significance of the Watuata forest from the viewpoint of its people. This study was conducted for a month using qualitative research methods implementing ethnographic research models. The ethnography includes observation, interviews, and library studies. The supporting instruments of this research are interview guidelines, voice recording equipment, cameras, and stationery.